Możliwości wykorzystania zróżnicowanych metod wielowymiarowej analizy statystycznej w badaniach społeczno-ekonomicznych : analiza porównywalności wyników - Grześkowiak, Alicja; Stanimir, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This paper presents the implementation of some multivariate techniques whose applications are determined by the measurement scales of analyzed variables. Some characteristic techniques were chosen according to the measurement scales: cluster analysis for ratio scale, correspondence analysis for nominal scale, logit and discriminant analysis for different types of scales. The analyzes were per-formed on the grounds of the same set of variables after carrying out the appropriate transformations of scales. This approach allowed us to compare the results obtained by usage of procedures for which application targets are specified. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (19); 2007; nr 1180, s. 31-42